Evaluación de riesgos por procesos en una empresa del sector privado avícola basado en la norma ISO 31000:2011 (2017)
This paper presents the risk assessment in a company of the poultry sector based on the NTC-ISO 31000: 2011, the identification, analysis and assessment of the inherent risks of the mission processes corresponding to a company dedicated to the production and commercialization of chicken eggs for consumption. Initially, the risks present in the mission processes are identified from internal information of the company; procedures, instructions and records provided by the organization as well as direct observation of the processes, interviews, findings and evidence.